Inhibition of biofouling on reverse osmosis membrane surfaces by germicidal ultraviolet light side-emitting optical fibers. (1st October 2022) - Rho, Hojung; Yu, Pingfeng; Zhao, Zhe; Lee, Chung-Seop; Chon, Kangmin; Perreault, François; Alvarez, Pedro J.J.; Amy, Gary; Westerhoff, Paul
Highlights: Novel RO membrane apparatus equipped with SEOFs were designed. Effects of UV-SEOFs on RO membrane biofouling were investigated. OH generated from UV-A SEOFs promoted microorganisms growth on RO membrane. OH affects degradation of RO membrane surface by passing through biofouling layer. UV-C SEOFs reduce biofouling on RO membrane, mitigating performance declines. Abstract: Biofouling of membrane surfaces poses significant operational challenges and costs for desalination and wastewater reuse applications. Ultraviolet (UV) light can control biofilms while reducing chemical usage and disinfection by-products, but light deliveries to membrane surfaces in spiral wound geometries has been a daunting challenge. Thin and flexible nano-enabled side-emitting optical fibers (SEOFs) are novel light delivery devices that enable disinfection or photocatalytic oxidation by radiating UV light from light-emitting diodes (LEDs). We envision SEOFs as an active membrane spacer to mitigate biofilm formation on reverse osmosis (RO) membranes. A lab-scale RO membrane apparatus equipped with SEOFs allowed comparison of UV-A (photocatalysis-enabled) versus UV-C (direct photolysis disinfection). Compared against systems without any light exposure, systems with UV-C light formed thinner—but denser—biofilms, prevented permeate flux declines due to biofouling, and maintained the highest salt rejection. Results were corroborated by in-situ optical coherence tomography and ex-situ measurements of biofilm growth on the membranes. Transcriptomic analysis showed that UV-C SEOFs down-regulated quorum sensing and surface attachment genes. In contrast, UV-A SEOFs upregulated quorum sensing, surface attachment, and oxidative stress genes, resulting in higher extracellular polymeric substances (EPS) accumulation on membrane surfaces. Overall, SEOFs that deliver a low fluence of UV-C light onto membrane surfaces are a promising non-chemical approach for mitigating biofouling formation on RO membranes. Graphical abstract: Image, graphical abstract